Regorafenib plus nivolumab in patients with mismatch repair-proficient/microsatellite stable metastatic colorectal cancer: a single-arm, open-label, multicentre phase 2 study. (April 2023) - Fakih, Marwan; Raghav, Kanwal Pratap Singh; Chang, David Z.; Larson, Tim; Cohn, Allen L.; Huyck, Timothy K.; Cosgrove, David; Fiorillo, Joseph A.; Tam, Rachel; D'Adamo, David; Sharma, Neelesh; Brennan, Barbara J.; et al.
Summary: Background: Anti-programmed cell death protein 1 antibodies plus multikinase inhibitors have shown encouraging activity in several tumour types, including colorectal cancer. This study assessed regorafenib plus nivolumab in patients with microsatellite stable/mismatch repair-proficient metastatic colorectal cancer. Methods: This single-arm, open-label, multicentre phase 2 study enrolled adults from 13 sites in the USA with previously treated advanced microsatellite stable/mismatch repair-proficient metastatic colorectal cancer. Eligible patients had known extended RAS and BRAF status, progression or intolerance to no more than two (for extended RAS mutant) or three (for extended RAS wild type) lines of systemic chemotherapy and an Eastern Cooperative Oncology Group performance status of 0 or 1. Regorafenib 80 mg/day was administered orally for 3 weeks on/1 week off (increased to 120 mg/day if 80 mg/day was well tolerated) with intravenous nivolumab 480 mg every 4 weeks. Primary endpoint was objective response rate. Secondary endpoints included safety, overall survival, and progression-free survival. Exploratory endpoints included biomarkers associated with antitumour activity. Patients who received at least one dose of study intervention were included in the efficacy and safety analyses. Tumour assessments were carried out every 8 weeks for the first year, and every 12 weeks thereafter until progressive disease/end of the study, and objective response rate was analysed after all patients had met the criteria for primary completion of five post-baseline scans and either 10-months' follow-up or drop out. This trial is registered with ClinicalTrials.gov, number NCT04126733 . Findings: Between 14 October 2019 and 14 January 2020, 94 patients were enrolled, 70 received treatment. Five patients had a partial response, yielding an objective response rate of 7% (95% CI 2.4–15.9; p = 0.27). All responders had no liver metastases at baseline. Median overall survival (data immature) and progression-free survival were 11.9 months (95% CI 7.0–not evaluable) and 1.8 months (95% CI 1.8–2.4), respectively. Most patients (97%, 68/70) experienced a treatment-related adverse event; 51% were grade 1 or 2, 40% were grade 3, 3% were grade 4, and 3% were grade 5. The most common (≥20%) events were fatigue (26/70), palmar-plantar erythrodysesthesia syndrome (19/70), maculopapular rash (17/70), increased blood bilirubin (14/70), and decreased appetite (14/70). Higher baseline expression of tumour biomarkers of immune sensitivity correlated with antitumour activity. Interpretation: Further studies are warranted to identify subgroups of patients with clinical characteristics or biomarkers that would benefit most from treatment with regorafenib plus nivolumab. Funding: Bayer /Bristol Myers Squibb .